Private Information, Capital Flows, and Exchange Rates - Gyntelberg, Jacob (IMF Working Papers; Working Paper ;, 2012)
We demonstrate empirically that not all capital flows influence exchange rates equally: Capital flows induced by foreign investors' stock market transactions have both an economically significant and a permanent impact on exchange rates, whereas capital flows induced by foreign investors' transactions in government bond markets do not. We relate these differences in the price impact of capital flows to differences in the amounts of private information conveyed by these flows. Our empirical findings are based on novel, daily-frequency datasets on prices and quantities of all transactions of foreign investors in the stock, bond, and onshore FX markets of Thailand.